The malectin-like receptor-like kinase LETUM1 modulates NLR protein SUMM2 activation via MEKK2 scaffolding - Liu, Jun; Huang, Yanyan; Kong, Liang; Yu, Xiao; Feng, Baomin; Liu, Derui; Zhao, Baoyu; Mendes, Giselle C.; Yuan, Peiguo; Ge, Dongdong; Wang, Wen-Ming; Fontes, Elizabeth P. B.; et al. (Nature plants, 2020)
The innate immune system detects pathogen-derived molecules via specialized immune receptors to prevent infections 1 – 3 . Plant immune receptors include cell surface-resident pattern recognition receptors (PRRs, including receptor-like kinases (RLKs)), and intracellular nucleotide-binding domain leucine-rich repeat proteins (NLRs). It remains enigmatic how RLK- and NLR-mediated signalling are connected. Disruption of an immune-activated MEKK1–MKK1/2–MPK4 MAPK cascade activates the NLR SUMM2 via the MAPK kinase kinase MEKK2, leading to autoimmunity 4 – 9 . To gain insights into the mechanisms underlying SUMM2 activation, we used an RNA interference-based genetic screen for mekk1 autoimmune suppressors and identified an uncharacterized malectin-like RLK, named LETUM1 (LET1), as a specific regulator of mekk1–mkk1/2 – mpk4 autoimmunity via complexing with both SUMM2 and MEKK2. MEKK2 scaffolds LET1 and SUMM2 for protein stability and association, and counter-regulates the F-box protein CPR1-mediated SUMM2 ubiquitination and degradation, thereby regulating SUMM2 accumulation and activation. Our study indicates that malectin-like RLK LET1 senses the perturbance of cellular homoeostasis caused by the deficiency in immune-activated signalling and activates the NLR SUMM2-mediated autoimmunity via MEKK2 scaffolding. Plants with loss of function mutations in the MEKK1–MKK1/2–MPK4 MAP kinase pathway show strong autoimmunity phenotypes and dwarfism. Through a suppressor genetic screen, the malectin-like receptor kinase LET1 is identified as a new regulator of immune signalling.